Transitivity Analysis in Four Selected Opinions about Jakarta Governor Election - Isti'anah, Arina (Journal of Language and Literature, 2014)
Jakarta governor election has been a popular topic recently. People who are interested in politics also comment the election. This paper attempts to analyze four selected opinions about the election, given by those who are interested in politics, by employing transitivity analysis. The method employed in this research was Critical Discourse Analysis which mainly focused on transitivity analysis. Based on the analysis, most opinions utilized material processes to show what Jakarta people expect from the governor, reflected by Actor-Goal, Affected, and Goal-Recipient participants. Relational process occurs in the data to attach Jakarta to its labels, shown by Carrier-Attribute participants. Verbal process reveals what the candidates assure when they win, by the appearance of Sayer-Verbiage. Mental process occurs with Jakarta as the Senser. Circumstances of purpose often exist in the data, indicating peoples expectation in the election. Keywords: transitivity, process, participant, circumstance